2022
DOI: 10.3390/bs12090331
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the Level of Physical Activity in Physically Active Older People

Abstract: There has not been much study of risk profiles in older people according to different levels of practice in physical activity. For this reason, the aim of this research was to evaluate whether the elements that influence the quality of life and factors such as gender and education can predict the level of physical activity in the physically active elderly population. The Fernández–Ballesteros quality of life questionnaire and the WHO International Physical Activity Questionnaire were applied to a sample of 397… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…This exercise intervention had value. Evidence shows that physical activity has an impact on regular physical activity in older adults [132,133]. As for the relationship between social support, emotion, and stress, previous studies have shown that social support could lower blood pressure in older adults [134], and could enhance the ability to adapt to stress [135], which also showed that social support helps to relieve stress and reduce depression [136].…”
Section: Discussionmentioning
confidence: 99%
“…This exercise intervention had value. Evidence shows that physical activity has an impact on regular physical activity in older adults [132,133]. As for the relationship between social support, emotion, and stress, previous studies have shown that social support could lower blood pressure in older adults [134], and could enhance the ability to adapt to stress [135], which also showed that social support helps to relieve stress and reduce depression [136].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, inflammatory process is also related to serum zinc level in the development of age-related chronic diseases [ 7 ]. Furthermore, physical activity should be taken into account in the geriatric population [ 8 , 9 ]. It has been found that impaired physical activity may be correlated with serum zinc levels [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Terefore, physical activity is one of the relevant quality of life components for older people [28]. Still, socio-contextual variables can infuence how much older people engage in physical activity, such as gender, educational level, functional capacity, and the practice of leisure activities, with older women and less-educated individuals exhibiting less proactive attitudes towards physical capacity and leisure activities [29]. Likewise, socioenvironmental factors related to a higher quality of life are related to more physical activity in older people, such as income, education, and practicing healthy lifestyle [30].…”
Section: Introductionmentioning
confidence: 99%